2006
DOI: 10.1074/jbc.m511192200
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the DIF Motif of the DnaJ (Hsp40) Co-chaperone in the Regulation of the DnaK (Hsp70) Chaperone Cycle

Abstract: To perform effectively as a molecular chaperone, DnaK (Hsp70) necessitates the assistance of its DnaJ (Hsp40) co-chaperone partner, which efficiently stimulates its intrinsically weak ATPase activity and facilitates its interaction with polypeptide substrates. In this study, we address the function of the conserved glycine-and phenyalanine-rich (G/F-rich) region of the Escherichia coli DnaJ in the DnaK chaperone cycle. We show that the G/F-rich region is critical for DnaJ co-chaperone functions in vivo and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 42 publications
2
57
0
1
Order By: Relevance
“…On the other hand, the role of the G/F-rich region in substrate binding seems controversial. Several reports have shown that this domain is dispensable since deletion or mutation of DIF motifs within this DnaJ domain did not modify the ability to bind either 32 or chemically unfolded luciferase (15,43). Similarly, Type I ERdj3 and Type II Sis1p bound several substrates independently of this domain (42,44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the role of the G/F-rich region in substrate binding seems controversial. Several reports have shown that this domain is dispensable since deletion or mutation of DIF motifs within this DnaJ domain did not modify the ability to bind either 32 or chemically unfolded luciferase (15,43). Similarly, Type I ERdj3 and Type II Sis1p bound several substrates independently of this domain (42,44).…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of DnaJ and Sis1p G/F-rich domain in E. coli and yeast cells, respectively, exhibits a poisonous effect (43,44). This effect was attributed to a possible role of the G/F-rich domain in the "targeting" of substrates to DnaK/Ssa1p and failure to activate the chaperone, which might result in kinetically trapped chaperone-substrate complexes (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility would be the Gly/Phe-rich linker between the J domain and central region, including an Asp-Ile-Phe tripeptide motif. Work with E. coli DnaJ and S. cerevisiae Ydj1 suggested that the Asp-Ile-Phe motif was important for the function of both co-chaperones, potentially for substrate transfer to the partner Hsp70s (38,39). The linker in the DJAs is conserved only in the type 1 co-chaperones, suggesting a mechanism unique to this class and not found in type 2 proteins such as DJB1.…”
Section: Discussionmentioning
confidence: 99%
“…DnaK-His was concentrated and stored at Ϫ70°C. DnaJ-His was purified from KY1456 cells harboring pKV2237 (pKV1142 trcp-dnaJ-his; the dnaJ gene with six histidine codons at the 3Ј-end) essentially as described (33).…”
Section: Methodsmentioning
confidence: 99%